Application of focused ion beam micromachining: a review - Rahman Azmil, Nur Atiqah; Jaafar, Israd Hakim; Ali, Mohammad Yeakub; Asfana, Banu (Trans Tech Publications, Switzerland, 2012)
Fabrication of micro and nanoscale components are in high demand for various applications in diversified fields that include automotive, electronics, communication and medicine. Focused ion beam (FIB) machining is one of the techniques for microfabrication of micro devices. This paper presents a review of FIB machining technology that include its parameter, responses, its important component systems, as well as the fundamentals of imaging, milling (etching) and deposition techniques. The application of FIB in micromachining is also presented.